Barriers and Facilitators to Implementation of Value-Based Care Models in New Medicaid Accountable Care Organizations in Massachusetts: A Study Protocol - Goff, Sarah L.; Gurewich, Deborah; Alcusky, Matthew; Kachoria, Aparna G.; Nicholson, Joanne; Himmelstein, Jay (Frontiers in Public Health, 2021)
Introduction Massachusetts established 17 new Medicaid accountable care organizations (ACOs) and 24 affiliated Community Partners (CPs) in 2018 as part of a large-scale healthcare reform effort to improve care value. The new ACOs will receive 1.8 billion dollars in state and federal funding over five years through the Delivery System Reform Incentive Program (DSRIP). The multi-faceted study described in this protocol aims to address gaps in knowledge about Medicaid ACOs’ impact on healthcare value by identifying barriers and facilitators to implementation and sustainment of the DSRIP-funded programs. Methods and Analysis The study’s four components are: (1) Document Review to characterize the ACOs and CPs; (2) Semi-structured Key Informant Interviews (KII) with ACO and CP leadership, state-level Medicaid administrators, and patients; (3) Site visits with selected ACOs and CPs; and (4) Surveys of ACO clinical teams and CP staff. The Consolidated Framework for Implementation Research’s (CFIR) serves as the study’s conceptual framework; its versatile menu of constructs, arranged across five domains (Intervention Characteristics, Inner Setting, Outer Setting, Characteristics of Individuals, and Processes) guides identification of barriers and facilitators across multiple organizational contexts. For example, KII interview guides focus on understanding how Inner and Outer Setting factors may impact implementation. Document Review analysis includes extraction and synthesis of ACO-specific DSRIP-funded programs (i.e., Intervention Characteristics); KIIs and site visit data will be qualitatively analyzed using thematic analytic techniques; surveys will be analyzed using descriptive statistics (e.g., counts, frequencies, means, standard deviations). Discussion Understanding barriers and facilitators to implementing and sustaining Medicaid ACOs with varied organizational structures will provide critical context for understanding the overall impact of the Medicaid ACO experiment in Massachusetts. It will also provide important insights for other states considering the ACO model for their Medicaid programs. Ethics and Dissemination IRB determinations were that the overall study did not constitute human subjects research and that each phase of primary data collection should be submitted for IRB review and approval. Study results will be disseminated through traditional channels such as peer reviewed journals, through publicly available reports on the mass.gov website; and directly to key stakeholders in ACO and CP leadership.